Expression profile of microRNA-29b and its action on matrix metalloproteinase 2 (MMP-2) in the cervical carcinogenic process (Research, Society and Development, 2021)
Background: Cervical cancer is the fourth most common cancer among women worldwide. In order to make the diagnosis earlier and more accurate, increase the prospect of using microRNA-29b, which targets matrix metalloproteinase-2 (MMP-2), proteolytic enzymes that play a significant role in the degradation of the important extracellular matrix in progression of cervical carcinogenic lesions. Objectives: The aim of this study was to evaluate the levels of expression of microRNA-29b at all histological levels of carcinogenesis and its relationship with MMP-2 in this type of cancer. Methods: RNA was extracted from eighteen paraffin-embedded biopsy samples diagnosed with carcinoma and 19 considerable healthy samples, after which a real-time PCR technician was performed for expression analysis. Results: Our results show underexpression of microRNA-29b and MMP-2. This decrease in expression was statistically significant and differentiated in the histopathological subtypes. In addition, it has been shown that MMP-2 is directly regulated by microRNA-29b. No other studies were found that performed the same analysis on cervical cancers. Conclusion: Our results indicate a potential diagnosis of microRNA-29b and MMP-2 for lesions and cervical cancer, and show a direct association between these molecules.